Performance evaluation of the novel multi-shaft mill using DEM modelling. (November 2016) - Bracey, R.J.; Weerasekara, N.S.; Powell, M.S.
Graphical Abstract: Multi-shaft EDS mill alongside DEM simulated ore particle flow. Highlights: Conducted a performance evaluation of the novel mill using site survey and DEM. Estimated the breakage energy environment through DEM simulations. Surveyed continuous mill operation under different operating conditions. Simulation revealed significant collisions greater than the critical breakage strength. Survey results comparable to the predicted P80 from the simulations. Abstract: Comminution is well known to be an inefficient process and a large consumer of energy globally, giving rise to the development of novel comminution devices trying to exploit this opportunity. A multi-shaft mill, considered to be a novel comminution device, combines a series of rotating shafts with attached flingers which impact gravity fed material. The mill offers positive benefits in terms of plant footprint, high reduction ratio, high throughput and potential benefits through ore specific circuit integration. A process performance evaluation was conducted by surveying the mill along with using Discrete Element Method (DEM) modelling. The survey proved the mills ability to continuously sustain operation and product size for two different ore types under various configurations. The DEM predicted that gravity fed material entering the multi-shaft mill, with 50% of particles accelerated to a velocity higher than 184 km/h and 10% higher than 299 km/h. These velocities are converted to comminution energy through collisions with liners or particle-particle interactions. Each particle is subject to more than 24 impacts per second, greater than the critical breakage strength of a particle (0.01 kW h/t), leading to potential efficient comminution. Significant numbers of collisions were simulated in the mill alongside significant breakage being recorded through the surveying of the mill, leading to a reasonable comparison of product size distributions from the simulated adsorbed collision energies compared to the survey data. Using this baseline of the mills performance evaluation methodology further simulation work will aim to better quantify the breakage environment through a full-scale simulation run in parallel with future proposed survey work which will address wear rates and tailored operating conditions for specific ore types.